THEORETICAL FOUNDATIONS OF READING COMPREHENSION - Mashrabjonova, Shaxrizoda (Журнал иностранных языков и лингвистики, 2021)
The article analyzes the existent problems in teaching reading comprehension and find the ways out of this problem by suggesting a series of exercises that can be useful in classroom activities.